Rodents and Other Vertebrate Invaders in the United States - Fall, Michael W.; Avery, Michael L.; Campbell, Tyler A.; Egan, Peter J.; Engeman, Richard M.; Pimentel, David; Pitt, William C.; Shwiff, Stephanie A.; Witmer, Gary W. (DigitalCommons@University of Nebraska - Lincoln, 2011)
Contents Introduction Assessing impacts of rodents and other vertebrate invaders Accounts of some important vertebrate invadersNorway rat (Rattus norvegicus)Roof rat (Rattus rattus)Polynesian rat (Rattus exulans)House mouse (Mus Musculus)Nutria (Myocastor coypus)Gambian giant pouched rat (Cricetomys gambianus)Feral swine (Sus scofa)Small Indian Mongoose (Herpestes javanicus)Rock pigeon (Columba livia)House sparrow (Passer domesticus)European starling (Sturnus vulgaris)Monk parakeet (Myiopsitta monachus)Brown tree snake (Boiga irregularis)Burmese python (Python molurus bivittatus)Coqui frog (Eleutherodactylus coqui)Sea lamprey (Petromyzon marinus)European and Asian carp (Cyprinidae) Offshore Threats